Miss Georgina's marriage dilemma - Shepherd, Eva (Shepherd, Eva. Rebellious young ladies., 2024)
"When fun-loving Miss Georgina risks losing her fortune unless she marries, her only option is getting wed to tightly wound Adam, Duke of Ravenswood. He needs her wealth to save his estate-but otherwise Georgina knows to stay out of his way. Except that's not in Georgina's nature... She'll find the joy and pleasure in anything, and for her that means in her marriage to Adam...and in their marriage bed!"--